Negotiation of National Identity of Teenager in the Context of Cyberspace in Border Territories of Indonesia-Malaysia - Sitti Syahar Inayah; Andi Muhammad Abdi; Saputranur Saputranur (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2021)
Social media is a primary choice of teenagers today to present their existence. Social media can depict one’s life, however, it shows character restriction which can be used. Furthermore, the sociocultural conditions of teenagers also contribute to identity disclosure. Therefore, negotiation of identity can be a choice when they want to present themselves. Thus, this research was designed to describe the negotiation of national identity performed by teenagers, particularly those living in the border territories of Indonesia-Malaysia through their social media accounts. This research is a qualitative study using a method of documentation. By using documentation, the analysis was focused on the language aspect and any relevant contexts to teenagers’ national identity. Documentation was performed in a way by interpreting or construing any existing texts, for instance, a photo of a red-and-white flag uploaded on a post. The results of the study suggested that the main dynamics of their national identity emerged from symbolic communication with other people. Therefore, the characteristic of people living in a border territory also affects the negotiation of their national identity. For example, the use of the neighboring country flag is not necessarily a threat. This is associated with the socio-cultural condition of the border society which is unique and likely affecting their national identity. By understanding such uniqueness, negative perception can be avoided when perceiving the usage of the neighboring country’s symbols.